An investigation of escape and scaling properties of a billiard system - Rolim Sales, Matheus [UNESP]; Borin, Daniel [UNESP]; da Costa, Diogo Ricardo [UNESP]; Szezech, José Danilo; Leonel, Edson Denis [UNESP] (AIP Publishing, 2024)
We investigate some statistical properties of escaping particles in a billiard system whose boundary is described by two control parameters with a hole on its boundary. Initially, we analyze the survival probability for different hole positions and sizes. We notice that the survival probability follows an exponential decay with a characteristic power-law tail when the hole is positioned partially or entirely over large stability islands in phase space. We find that the survival probability exhibits scaling invariance with respect to the hole size. In contrast, the survival probability for holes placed in predominantly chaotic regions deviates from the exponential decay. We introduce two holes simultaneously and investigate the complexity of the escape basins for different hole sizes and control parameters by means of the basin entropy and the basin boundary entropy. We find a non-trivial relation between these entropies and the system’s parameters and show that the basin entropy exhibits scaling invariance for a specific control parameter interval.